Myocardial Perfusion SPECT 2024 in Germany: Results of the 10th Survey - Lindner, Oliver; Gutberlet, Matthias; Burchert, Wolfgang; Derlin, Thorsten; Rischpler, Christoph (Nuklearmedizin - NuclearMedicine, 2025)
This paper presents the results of the 10th survey of myocardial perfusion SPECT (MPS) from the year 2024.A total of 198 questionnaires were evaluated, comprising 115 practices (PR), 57 hospitals (HO) and 26 university hospitals (UH). The results of the previous survey 2021 are shown in squared brackets.MPS data from 128.707 [133.057] patients (–3.3%) with 125.175 [131.868] stress and 102.903 [106.546] rest MPS were analysed. A comparison with official data revealed that 53% of all MPS were recorded. From 2018 to 2024, official data showed an increase in MPS every year. In 2024, on average, 650 [610] MPS patients (+7%) were examined in each department. Of the participating departments, 69% [74%] reported an increase or no changes in their patient numbers. As always ambulatory care cardiologists represented the major referral group (68% [69%]). Pharmacological stress was performed more frequently than ergometry (43% [42%]). Regadenoson was mostly used. The use of the different protocols remained almost unchanged. Two-day protocols were predominantly applied (49% [49%]). Multi-head cameras were used in (56% [58%] of the departments and SPECT-CT systems in (31% [28%]). Attenuation correction was performed in 35% [33%] of all MPS. 95% [89%] of all stress, 93% [88%] of all rest and 92% [87%] of all stress and rest scan were acquired as gated SPECT. 84% [72%] of the departments performed scoring by default. The proportion of departments not scoring decreased to 4% [13%].The MPS 2024 survey indicates that the long-term positive development of MPS imaging is continuing. The procedural and technical details of MPS imaging demonstrate a high level of conformity with guidelines, with a slight improvement observed from 2021 to 2024.
Keywords: Myocardial perfusion SPECT; utilization review; utilization statistics; numerical data; ATTR imaging